PENGARUH RETURN ON INVESTMENT (ROI), RETURN ON EQUITY (ROE) DAN LEVERAGE TERHADAP RETURN SAHAMâ€ (Studi Normatif Perusahaan Manufaktur Sub Sektor Farmasi Bursa Efek Indonesia Tahun 2015-2019) - Eka Tarika Ilham Abidin; Nina Adelina (Riset Manajemen dan Akuntansi, 2022)
The share price is the price of a share that occurs on the stock market at a certain time by market participants. (Kurnia, 2019). Shares are part of the owner in the company, where each share gives voting rights to the owner of the share. Return has its own advantages so that investors can enjoy the investment that can be made. Investment will provide benefits with various levels, of course, investors (investors) will not invest. So that the investment, whether it is in a short time or continuously with the main aim of obtaining profits, is referred to as reciprocity, either directly or indirectly. Descriptive statistics convey an explanation of a data that can be observed from the number of average values (mean), the size of the digression, maximum, minimum, describing the standard to prove whether the allocation variable is normal or there are constraints. The description of descriptive statistics was carried out on the population used in this study, namely the pharmaceutical sub-sector manufacturing companies listed on the Indonesian stock exchange from 2015 to 2019. This study uses stock returns as the dependent variable, while the independent variable is return on investment (ROI). ), return on equity (ROE) and leverage.